The innovative performance of China's national innovation system - Philipp Boeing; Philipp Sandner (Frankfurt School of Finance & Management, 2011)
The objective of this paper is to investigate the innovative performance of China's NIS in international comparison and the capacity of China's NIS in creating indigenous innovation. We provide insights drawing upon patent data and using patent families to determine the value of the underlying invention. For the timeframe we studied, China's comparative advantage exists in the creation of low value innovative performance, albeit increasingly in huge quantities. Constantly rising volumes of patent applications mirror both, the improved protection of intellectual property rights and increasing capacity for inventiveness. Supplemented by the continuous growth of the Chinese economy, improving conditions are reflected and reinforced by more R&D-intense FDI. Foreign firms' innovative performance associated with higher economic value is particularly strong.
Keywords: O53; O47; O34; P27; 330; National Innovation System; Innovative Performance; China; Patents; Innovation Policy